2021
DOI: 10.1002/1873-3468.14103
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinases in a journey to combat arthropod‐borne pathogen transmission

Abstract: Ixodes scapularis ticks feed on humans and other vertebrate hosts and transmit several pathogens of public health concern. Tick saliva is a complex mixture of bioactive proteins, lipids and immunomodulators, such as I. scapularis sphingomyelinase (IsSMase)-like protein, an ortholog of dermonecrotoxin SMase D found in the venom of Loxosceles spp. of spiders. IsSMase modulates the host immune response towards Th2, which suppresses Th1-mediated cytokines to facilitate pathogen transmission. Arboviruses utilize ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 200 publications
(232 reference statements)
0
2
0
Order By: Relevance
“…In addition to spiders, SMase D/PLDs (and homologous genes/peptides) have been found in many other organisms (Cordes and Binford, 2018), although apparently not (so far) mammals (McDermott et al, 2020). These include bacteria (Flores-Diaz et al, 2016;Mariutti et al, 2017), fungi (Dias-Lopes et al, 2013), and some other arthropods, most notably tick saliva (Alarcon-Chaidez et al, 2009;Rajendran et al, 2021;Regmi et al, 2020) and scorpions (Ben Yekhlef et al, 2020;Borchani et al, 2011). Some of these SMases D/PLDs have been established to have activities similar to the sicariid spiders, but most have not been fully characterized.…”
Section: Spiders and Other Organisms That Produce Smase Dmentioning
confidence: 99%
“…In addition to spiders, SMase D/PLDs (and homologous genes/peptides) have been found in many other organisms (Cordes and Binford, 2018), although apparently not (so far) mammals (McDermott et al, 2020). These include bacteria (Flores-Diaz et al, 2016;Mariutti et al, 2017), fungi (Dias-Lopes et al, 2013), and some other arthropods, most notably tick saliva (Alarcon-Chaidez et al, 2009;Rajendran et al, 2021;Regmi et al, 2020) and scorpions (Ben Yekhlef et al, 2020;Borchani et al, 2011). Some of these SMases D/PLDs have been established to have activities similar to the sicariid spiders, but most have not been fully characterized.…”
Section: Spiders and Other Organisms That Produce Smase Dmentioning
confidence: 99%
“…Briefly, as ticks attaches and starts feeding, they secrete salivary molecules in saliva. In addition, ticks also secrete exosomes carrying various components including RNA, protein, peptides and miRNA ( Sultana and Neelakanta, 2020 ; Ahmed et al., 2021 ; Rajendran et al., 2021 ). These exosomes could either fuse with the host cells and release content into the host cell or contents are released as soon as tick exosomes enters the vertebrate host.…”
Section: Anti-tick Vaccinementioning
confidence: 99%
“…Our findings revealed that tick exosomes are salivary/saliva components and that they do facilitate pathogen transmission to the vertebrate host, suggesting that they are novel means of the dissemination from vector to the vertebrate host [3,24] . Treatment of arthropod/neuronal exosomes with GW4869 (a pharmacological agent that interferes with the production and release of exosomes) inhibits the viral RNA/proteins and also interferes with the transmission of flaviviruses from exosomes to the naïve recipient host cells [2][3][4]25,48,49] . The mechanism(s) of GW4869 affecting viral transmission has not been clearly understood.…”
Section: Introductionmentioning
confidence: 99%